Une Femme Pionnière Dans Le Monde Des Arts, Baya 1931-1998 Eléments De Contextualisation - Bouayed, Anissa (جامعة عبد الحميد مهري - قسنطينة 2, 2017)
باية هي أول امرأة جزائرية فرضت نفسها كفنانة في عهد الاستعمار. ليس الهدف من هذا المقال هو تحليل إنتاجها وإنما كيفية تميزها في عالم فني تم التفكير فيه وبنائه دون الأغلبية العربية -المسلمة من سكان الجزائر، من باب أولى النساء. كيف نظر إليها؟ وبأي تناقض وازدواجية؟ سنركز هنا، ليس فقط على لحظة "اكتشافها"، كنقطة انطلاق لسيرورة تميزها كفنانة؛ وإنما عند مجمل مسارها الذي اتسم بفترات إبداع وأخرى للانطواء. مسار منكسر يعبر عن الصعوبة الجمة -في تلك الظروف -أن تكون (باية) في نفس الوقت امرأة جزائرية وفنانة بأتم معنى الكلمة.
Baya was the first Algerian woman to impose herself as an artist during the period of colonisation. The present work will not analyse her artistic production, but rather how she entered the art community in which the Muslim Arab majority was left behind. How was it perceived? Here, we will focus not only on the time of her “discovery” – starting point of the individuation process as an artist– but also on her entire artistic career, marked with moments of creation et periods of withdrawal. Her artistic career reveals the difficulties, during that period, to be both an Algerian woman and an artist in her own right.
Keywords: الفن التشكيلى -- المرأة الجزائرية -- الرسامون الجزائريين -- الاستعمار الفرنسى -- الجزائر